2006
DOI: 10.1007/s11547-006-0042-3
|View full text |Cite
|
Sign up to set email alerts
|

Multidetector–row CT angiography of renal artery stenosis in 50 consecutive patients: prospective interobserver comparison with DSA

Abstract: MDCT angiography is very accurate and robust, even for the assessment of renal artery stenosis, and has the potential to become a viable substitute, in most cases, for diagnostic catheter-based DSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 19 publications
1
15
0
3
Order By: Relevance
“…Multidetector scanners have advanced the imaging clarity in computed tomography, making it possible to visualize vascular structures in detail. Multidetector computed tomography (MDCT) is a reliable and noninvasive tool for diagnosing renal artery variations and pathologies [4] . We present a case of a rare arterial variation in whom the renal artery arose from the inferior mesenteric artery (IMA) and common iliac artery (CIA).…”
Section: Introductionmentioning
confidence: 99%
“…Multidetector scanners have advanced the imaging clarity in computed tomography, making it possible to visualize vascular structures in detail. Multidetector computed tomography (MDCT) is a reliable and noninvasive tool for diagnosing renal artery variations and pathologies [4] . We present a case of a rare arterial variation in whom the renal artery arose from the inferior mesenteric artery (IMA) and common iliac artery (CIA).…”
Section: Introductionmentioning
confidence: 99%
“…Another complicating factor in this study is the use of differing imaging modalities for each study cohort for determining the presence of FMD (CTA versus catheter-based angiography). However, several prior studies [21][22][23] have shown that CTA is a reliable diagnostic modality for detecting renal atherosclerotic and FMD lesions. A recent study 23 demonstrated that CTA detected 100% of the 40 FMD lesions that were detected by catheter-based angiography in a population of 21 hypertensive FMD patients.…”
Section: Discussionmentioning
confidence: 97%
“…Arteriosklerotische Wandveränderungen und Stenosierungen treten dabei bevorzugt am Abgang und innerhalb der ersten 2 cm der Nierenarterien auf [27] und sind durch die MDCT-Angiographie gut darstellbar. Die diagnostische Wertigkeit der MDCT-Angiographie reicht bei adäquater Untersuchungstechnik an die der konventionellen Angiographie heran [9]. Zunehmend gewinnt auch die MR-Angiographie an Bedeutung.…”
Section: Vaskuläre Prozesseunclassified
“…Sie ist gekennzeichnet durch ein perlschnurartiges Abb. 9 9 Transplantatniere rechtsseitig im Becken. Gut zu erkennen ist ein nach KMGabe hypodens erscheinender, kapselüberschreitender Prozess (Pfeil) der einem Nierenzellkarzinom entspricht (histologisch gesichert) Abb.…”
Section: Vaskuläre Prozesseunclassified